Randomized control trial to compare effects of ultra-low dose (Ethinylestradiol 20 μg or 15 μg) with low dose (Ethinylestradiol 30 μg) hormonal pills on lipid discordance in non-obese PCOS women - Subhankar Dasgupta; Joyeeta Mondal; Barnali Goswami; Jija Dasgupta (Korean Society of Obstetrics and Gynecology, 2023)
Objective Regular users of hormonal contraceptive pills show marked heterogeneity in metabolic effects with variations in compositions. This might be due to choice of outcome variables for comparison. Total cholesterol-high-density lipoprotein ratio (TC/HDL) discordance with low-density lipoprotein (LDL-C) has now become an established marker of future risk for atherosclerotic cardiovascular disease and stable to variations in user. Methods The present study was a randomized controlled trial to compare prevalence of TC/HDL and LDL discordance among non-obese women with polycystic ovarian syndrome (PCOS) treated with hormonal pills. Women were randomized into three arms, two arms received ultra-low dose pills (Ethinylestradiol [EE] 20 μg with drosperinone 3 mg or EE 15 μg with gestodene 60 μg) and one arm received low dose pill (EE 30 μg with desogestrel 150 μg). The role of baseline participant features and pill composition on discordance was determined. Results Discordance was observed in more than a quarter of the participants before intervention. After 1 year of treatment, less than a fifth of the participants were discordant. Ultralow-dose pill users had lower discordance, LDL, and TC than low-dose pill users after 1 year of treatment. The random forest, a non-linear classifier, showed the highest accuracy in predicting discordance. The baseline Parameters with the maximal impact on the occurrence of discordance were triglyceride, homeostatic model assessment for insulin resistance, body mass index, and high density lipoprotein. Conclusion Non-obese PCOS women on ultra-low dose pill have a lower risk of acquiring future atherosclerotic cardiovascular disease.